Entrepreneurs personality traits and business performance: a conceptual framework / Siti Farah Edwin, Jati Kasuma Ali and Norlina Mohamed Noor - Edwin, Siti Farah; Ali, Jati Kasuma; Mohamed Noor, Norlina (Universiti Teknologi MARA, 2021)
The Big Five Model, also known as broad traits which consist of extroversion, emotional stability, openness to experience, agreeableness, and conscientiousness. However, this paper suggest that specific personality traits are more suitable in entrepreneurship research than broad traits. Distal dispositions are non cognitive and non-ability dispositions that have an indirect impact on behavior and performance. Hence, personality traits should be linked to the start-up and performance of a firm. As a result, the goal of this research is to start a conversation about entrepreneur personality, which is largely constituted of independent entrepreneurs that want to expand their businesses. The present paper, therefore, contributes to the literature on sustainability by recommending a conceptual framework towards greater sustainability performance of the business entrepreneurs. Hoped this paper can provide some insights into factors leading to entrepreneurs' business performance, also as guide for implementation of programs and policies to increase the number of entrepreneurship involvement as long-term objective in Malaysia.